Siri' Na Pacce Culture In The Practice Of Forced Marriage Of Minors: A Challenge To The Protection Of Women's And Children's Rights - Muh Alghifari; Andi Agung Mallongi; Dewi Putriani; Saipul Saipul (Authentica: Private Law Journal, 2025)
This study examines the philosophy of siri’ na pacce within the context of the Bugis Makassar society, which is a time-honored heritage regulating social actions and behavior. Siri’ na pacce, which literally means a sense of shame and pain, is more deeply understood as dignity and honor. In Bugis Makassar society, siri’ na pacce significantly influences perspectives and practices related to marriage, where family honor is highly esteemed. However, the implementation of siri’ na pacce values does not always lead to positive outcomes, as evidenced by the widespread phenomenon of forced child marriages. Data from the Makassar High Religious Court in 2022 shows there were 2,663 applications for child marriage dispensation, 96% of which were approved. Reports from the Ministry of Women’s Empowerment and Child Protection (PPP) indicate that South Sulawesi is one of the provinces with the highest number of marriage dispensation requests. Forced child marriages are considered an effective way to maintain and restore family honor in response to social and technological developments that influence gender interactions. This study uses a qualitative method with a socio-legal approach to understand the social phenomena in the field related to siri’ na pacce culture and the challenges in protecting the rights of women and children. The findings of this study are expected to provide a deeper understanding of the impact of siri’ na pacce culture on the practice of forced marriages and its implications for the protection of women's and children's rights in Bugis Makassar society.